2022
DOI: 10.3390/healthcare10112164
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence in Screening for Adverse Perinatal Outcomes—A Systematic Review

Abstract: (1) Background: AI-based solutions could become crucial for the prediction of pregnancy disorders and complications. This study investigated the evidence for applying artificial intelligence methods in obstetric pregnancy risk assessment and adverse pregnancy outcome prediction. (2) Methods: Authors screened the following databases: Pubmed/MEDLINE, Web of Science, Cochrane Library, EMBASE, and Google Scholar. This study included all the evaluative studies comparing artificial intelligence methods in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…A recent scoping review mentioned that AI can be used to address health inequalities in primary care 70 . Other literature reviews in high‐income settings have found that m‐health reduced hospital admission, increased doctor‐patient relationships, and improved risk assessment 71–73 . We found mobile applications and texting increase clinic attendance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A recent scoping review mentioned that AI can be used to address health inequalities in primary care 70 . Other literature reviews in high‐income settings have found that m‐health reduced hospital admission, increased doctor‐patient relationships, and improved risk assessment 71–73 . We found mobile applications and texting increase clinic attendance.…”
Section: Discussionmentioning
confidence: 67%
“…70 Other literature reviews in high-income settings have found that m-health reduced hospital admission, increased doctor-patient relationships, and improved risk assessment. [71][72][73] We found mobile applications and texting increase clinic attendance. A similar systematic review documented a consistent improvement of clinic attendance at healthcare appointments by text message reminders irrespective of types of healthcare level.…”
Section: Agreement and Disagreement With Available Studiesmentioning
confidence: 85%
“…The correlation of currently known biomarkers and CBR expression might help improve PTB prediction and, subsequently, neonatal outcomes. Using artificial intelligence methods, such as machine learning, might help refine the prognostic value of the existing clinical risk factors of PTB, especially in combination with biomarker analysis [ 54 , 55 ]. Moreover, Villar et al proposed the phenotypic classification of PTB [ 56 ], where identifying and classifying patients according to their distinct phenotypes could improve the management of PTB.…”
Section: Discussionmentioning
confidence: 99%
“…It provides an ample understanding of genetic factors that may affect the developing fetus. 39 , 45 AI analyze genetic data to identify potential risks and inform expectant parents about genetic conditions that might be present. For instance, a study tested a feedforward neural network dependent on genetic algorithms on 381 pregnant women.…”
Section: Ai-based Prenatal Screeningmentioning
confidence: 99%